2021
DOI: 10.1186/s12879-021-06043-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic stewardship program in Pakistan: a multicenter qualitative study exploring medical doctors’ knowledge, perception and practices

Abstract: Background The emerging threat of antibiotic resistance is growing exponentially and antibiotic stewardship programs are cornerstone to fight against this global threat. The study aimed to explore the knowledge, perspectives and practices of physicians regarding various aspects of antibiotic stewardship program including antibiotic stewardship activities, rational use of antibiotics, antibiotic resistance, prescribing practices and factors associated with these practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 48 publications
2
49
1
Order By: Relevance
“…This finding is supported by published studies elsewhere ( 28 , 41 , 46 , 56 , 57 ). One of the possible reasons of developing adverse events in this sub-group of patients might be due to polypharmacy and resultant drug–drug interactions ( 54 , 58 , 59 ). In addition, our study findings demonstrated that employed patients tend to experience more adverse events as compared with unemployed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by published studies elsewhere ( 28 , 41 , 46 , 56 , 57 ). One of the possible reasons of developing adverse events in this sub-group of patients might be due to polypharmacy and resultant drug–drug interactions ( 54 , 58 , 59 ). In addition, our study findings demonstrated that employed patients tend to experience more adverse events as compared with unemployed.…”
Section: Discussionmentioning
confidence: 99%
“…Purposive sampling accompanied by convenience sampling was used to engage participants [ 40 ]. In the first stage, all healthcare professionals (HCPs) were purposively approached during working hours through telephone call or personal visit and invited to participate after explaining the brief intent of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, other studies conducted in Pakistan, India, Hungary, and the US also reported high level of resistance to these antibiotics (39)(40)(41)(42)(43). The probable reason for increased antibiotic resistance could be an excess, inappropriate use and careless selection of antibiotics (44), as a number of studies have reported irrational prescribing, dispensing and use of antibiotics in Pakistan (45)(46)(47)(48). The rapidly growing antibiotic resistance in Pakistan demand effective implementation of antibiotic stewardship program in accordance with the recommendations of the WHO (49-51).…”
Section: Discussionmentioning
confidence: 74%